Optimalisasi Pengembangan Aset Negara di Kota Kendari: Model Analisis Highest and Best Uses - Intihanah; Akhmad Khanafi Yusuf; Mulyati Akib (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the optimization of state asset development using the highest and best uses analysis model. The method used is a qualitative approach, involving sources and informants as data sources by means of interviews, and direct field research is conducted to analyze the optimization of state asset development. Based on the results of the productivity analysis, 2 alternative uses were obtained, namely office complexes and mix-use development (sports centers, shops and fitness centers). The results of the analysis show that the mix-use development alternative is the optimal choice in developing these assets. This is based on several advantages, including: providing more significant added value for investors, generating a rate of return that exceeds minimum expectations, offering a higher return on investment ratio, having a shorter payback period than the office complex alternative, and contributing to state revenue through Non-Tax State Revenue.